Solid‐State Molecular Nanomagnet Inclusion into a Magnetic Metal–Organic Framework: Interplay of the Magnetic Properties. Issue 2 (25th November 2015) - Mon, Marta; Pascual‐Álvarez, Alejandro; Grancha, Thais; Cano, Joan; Ferrando‐Soria, Jesús; Lloret, Francesc; Gascon, Jorge; Pasán, Jorge; Armentano, Donatella; Pardo, Emilio
Abstract: Single‐ion magnets (SIMs) are the smallest possible magnetic devices and are a controllable, bottom‐up approach to nanoscale magnetism with potential applications in quantum computing and high‐density information storage. In this work, we take advantage of the promising, but yet insufficiently explored, solid‐state chemistry of metal–organic frameworks (MOFs) to report the single‐crystal to single‐crystal inclusion of such molecular nanomagnets within the pores of a magnetic MOF. The resulting host–guest supramolecular aggregate is used as a playground in the first in‐depth study on the interplay between the internal magnetic field created by the long‐range magnetic ordering of the structured MOF and the slow magnetic relaxation of the SIM. Abstract : Molecular magnetism meets MOFs ! A unique example of solid‐state incorporation of a single‐ion magnet (SIM) within the pores of a magnetic 3D MOF in a single‐crystal to single‐crystal process is shown. The resulting host–guest supramolecular aggregate affords the first deep study on the interplay between the internal magnetic field of the MOF and the slow magnetic relaxation of the SIM (see figure).